Pollinator-Mediated Interactions Between Alien and Native Plants: Alien Status and Spatial Relationships - Charlebois, Julia (Université d'Ottawa / University of Ottawa, 2017)
The introduction of species outside of their native ranges has been extensively studied in ecology. Particular attention has been paid to examining interactions between alien and native plants, and a large proportion of this attention has focused on pollinator-mediated interactions. In order to interact through pollinators, plants must co-occur, coflower, and share pollinators; studies investigating pollinator-mediated interactions between alien and native plants frequently make fundamental assumptions about the definition of these prerequisites to pollinator-mediated interaction. The present analysis examines assumptions about plant co-occurrence and the effects that these assumptions have on study outcomes. In Chapter 2, I present the results of a meta-analysis of 76 studies which overturns previous findings that pollinator-mediated interactions between plants can be predicted on the basis of whether the neighbour is an alien, phylogenetic distance, or floral trait similarity. Moreover, I demonstrate that the spatial definition of the control group (i.e. the distance between the group of focal plants that ‘do not co-occur’ with the alien/alternate neighbour species and the nearest individuals of that neighbour species), and the spatial arrangements of plants within their treatment groups (i.e. the relative placement of the group of focal plants that ‘co-occurr’ with the neighbour species), both have a significant impact on the outcome of pollinator-mediated interactions between alien and native plants. I also emphasize evidence of bias in the selection of study systems and in the process of publication. In Chapter 3, I present the results of a field experiment testing the role of distance between interacting plants in determining patterns of visitation by insects. The results of this analysis are suggestive of visitor functional group-dependent effects but limited by low power. In both Chapter 2 and Chapter 3, I show that heretofore unexamined assumptions about definitions of co-occurrence of plants may be introducing bias into studies of pollinator-mediated interactions between plants, and that facilitation and competition between plants for visitation may be linked across different spatial scales.
Keywords: Pollination; Pollinator-mediated interactions; Methods; Spatial scale; Alien plants; Alien-native interactions; Meta-analysis